緊急対応を要した下顎骨動静脈奇形の1例 - 長谷川, 和樹; 原田, 清; 名生, 邦彦; 宮本, 日出雄 (日本口腔外科学会雑誌, 2013)
Arteriovenous malformation (AVM) of the jaw is considered a rare lesion. We report a case of AVM of the mandible. A 51-year-old man was referred to our department for further evaluation of a mandibular lesion. Panoramic radiography showed a multilocular radiolucency extending from the lower retromolar region to the right ramus of the mandible. A biopsy was performed for differential diagnosis between an ameloblastoma and keratocystic odontogenic tumor. However, severe hemorrhage occurred during the biopsy. The patient was admitted to our hospital urgently. An intraosseous AVM supplied by the maxillary artery was suspected on angiography. Embolization of the right maxillary artery was performed to decrease the hemorrhage during operation. One hour after the embolization, a segmental mandibulectomy was perfomed with the patient under general anesthesia. Histopathologically, the lesion was diagnosed as an AVM. The patient was followed up for 2 years without recurrence.